Transcription factors involved in plant responses to cadmium-induced oxidative stress - Zhang, Hewan; Lu, Lingli (Frontiers in Plant Science, 2024)
Cadmium (Cd) is a heavy metal highly toxic to living organisms. Cd pollution of soils has become a serious problem worldwide, posing a severe threat to crop production and human health. When plants are poisoned by Cd, their growth and development are inhibited, chloroplasts are severely damaged, and respiration and photosynthesis are negatively affected. Therefore, elucidating the molecular mechanisms that underlie Cd tolerance in plants is important. Transcription factors can bind to specific plant cis-acting genes. Transcription factors are frequently reported to be involved in various signaling pathways involved in plant growth and development. Their role in the resistance to environmental stress factors, particularly Cd, should not be underestimated. The roles of several transcription factor families in the regulation of plant resistance to Cd stress have been widely demonstrated. In this review, we summarize the mechanisms of five major transcription factor families–WRKY, ERF, MYB, bHLH, and bZIP–in plant resistance to Cd stress to provide useful information for using molecular techniques to solve Cd pollution problems in the future. .